Políticas públicas de incentivo a produção da bovinocultura leiteira nas regiões do Oeste e Sudoeste do Estado do Paraná: do compromisso público a execução dos processos governamentais - Neukirchen, Leandro Cesar (2022)
This study aims to analyze the public policy process forming from the social commitment assumed to the execution, highlighting the rationality that guides this process in Brazil. To do so, the analysis of the public policy to encourage milk production and milk distribution in Brazil is taken as a cut. More specifically, we seek to study the institution and implementation encourage milk production in the Paraná state, analyzing the cities of Cascavel, Marechal Rondon and Toledo in the Paraná West and Francisco Beltrão, in the Southwest. We intended to present the public policies results in which there are structural problems that compromise the public resources use. The theoretical foundation is based on an interdisciplinary view, addressing the importance, cost, and production of State public policies, as well as the role society in this process. the methodology used to develop this study was based on the Executive Assessment method, developed by the federal government to encourage social participation in the country's decision-making processes. This method has ten verification steps that examine from the legislator’s conception and intentions to the results obtained and provides for the evaluator's recommendation on problems, seeking to improve political processes. We verified that the different governmental spheres do not interact with each other and do not have parameters for controlling and verifying the social investment results. We also note nonexistence of a responsibilities division in the different parts of public management and a limitation in the legislation that authorizes this polices. Considering that rulers are authorized by the vote, the need to motivate society's participation in political processes is emphasized, since good or bad results come from a democratic process.